PERAN DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI DALAM PENYELENGGARAAN HUBUNGAN INDUSTRIAL DI KAB. INDRAGIRI HULU - Mardiansyah, Ogi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Worker or laborer is quite important corporate asset, but in fact often the things that can cause industrial relations problems such as lack of remuneration, termination of employment, and so on. Therefore, the local government through establishing government agencies related to the Social Service Manpower Indragiri Hulu acts as a mediator organization of industrial relations should be able to play an active role in helping to resolve the existing problems in Indragiri Hulu. To determine the role of the Social Department of Manpower and Transmigration as the organization of industrial relations in Indragiri Hulu, the authors conducted a study entitled "The Role of Social Service Manpower and Transmigration in the Implementation of Industrial Relations in the district. Inhuâ€.This type of research is a qualitative study, which was conducted at the Department of Manpower and Transmigration Social District. Inhu, then for the analysis techniques presented the data in the form of exposure or overview of the findings of the field in the form of data and information on interviews, documentation based on existing conditions. Based on the research that has been conducted to conclude that the Social Service Manpower his best role as meditor implementation in industrial relations, but there are several factors inhibiting the role of the Social Department of Manpower and Transmigration as a mediator implementation of industrial relations, namely: (a) There is still a lack of awareness and responsibility of the company (b) the lack of compliance by the disputing parties to the negotiation plan established mediators (c) lack of understanding and comprehension of the rush (d) lack of adequate personnel resources assigned as mediator functional employees.Keywords: Role, Organization, Mediators